REST API Development with Node.js Manage and Understand the Full Capabilities of Successful REST Development - Doglio, Fernando (Apress, 2018)
Manage and understand the full capabilities of successful REST development. REST API development is a hot topic in the programming world, but not many resources exist for developers to really understand how you can leverage the advantages. This completely updated second edition provides a brief background on REST and the tools it provides (well known and not so well known), then explains how there is more to REST than just JSON and URLs. You will learn about the maintained modules currently available in the npm community, including Express, Restify, Vatican, and Swagger. Finally you will code an example API from start to finish, using a subset of the tools covered. The Node community is currently flooded with modules; some of them are published once and never updated again - cluttering the entire universe of packages. Pro REST API Development with Node.js shines light into that black hole of modules for the developers trying to create an API. Understand REST API development with Node.js using this book today. .